Improving the precision of search strategies for guideline surveillance. (14th November 2020) - Casey, Monica; Raynor, Michael; Jacob, Catherine; Sharp, Stephen; McFarlane, Emma
Abstract : Introduction and aim: NICE guideline surveillance determines whether previously published guidelines need updating. The surveillance process must balance time constraints with methodological rigor. It includes a rapid review to identify new evidence to contradict, reinforce or clarify guideline recommendations. Despite this approach, the screening burden can still be high. Applying additional search techniques may increase the precision of the database searches. Methods: A retrospective analysis was conducted on five surveillance reviews with less than 2% of the studies included after screening. Modified searches were run in MEDLINE, Embase and PsycINFO (where appropriate) to test the impact of additional search techniques: focused subject headings, subheadings, frequency operators and title only searches. Modified searches were compared to original search results to determine: the retrieval of included studies, the precision of the search and the number needed to read. Studies not retrieved by the modified search were checked to determine if the surveillance decision would have been affected. Results: The additional search techniques tested indicated that a combination of focused subject headings and frequency operators could improve the precision of surveillance searches. The modified search retrieved all the original studies included in the surveillance review for three of the reviews tested. Some of the original included studies were not retrieved for two reviews but the missing studies would not have affected the surveillance decision. Conclusions: Combining focused subject headings and frequency operators is a viable option for improving the precision of surveillance searches without compromising recall and without impacting the surveillance decision.